Knowledge and Practices of Biomedical Wastemanagement among Nurses in Tertiary Level Hospitals - Islam, Md. Sirazul; Khanam, Dr. Fahmida; Islam, Dr. ANM Shamsul; Sheik, Md. Safiqul Islam; Kumar, Sreekato (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Biomedical waste (BMW) management is not just a legal need, but also a social responsibility. Utilizing the skills and knowledge of nursing practice, nurse can enhance proper BMW management while minimizing complications related to infectious wastes. Methods: A descriptive type of cross sectional study was conducted among 297 nurses working in Dhaka Medical College and Hospital and Shaheed Suhrawardy Medical College and Hospital, in Dhaka city. Data were collected with a pretested semi-structured questionnaire and practices were assessed by observational checklist. Results: Majority (58.6%) of the participants were belongs to age group 25-35 years. Only 4% had right knowledge about six types color coding bin for BMW storage according to national guideline for BMW management. Regarding practice 56% did not store waste in designated color coded bin, 53% recapped used needle, 93% didn’t practice needle cutter, 47% not wear PPE. About barriers of BMWM 64% of respondents opined for inadequate nursing and support staff, of them 41% were well-trained, 35% stated that dedicated place for temporary storage. Conclusion: Most of the nurses had knowledge of BMW and its management but less practice due to the unavailability of sufficient trained staff, logistics, designated places etc